Pre-Service English Teachers’ Motivations Toward the Teaching Profession - Ayuningtyas, Hartini; Santosa, Imam (STAIRS: English Language Education Journal, 2023)
This study investigates the motivations of pre-service English teachers at Esa Unggul University, Indonesia, after completing the teaching practicum. A mixed methods approach was employed, combining qualitative interviews and quantitative questionnaires with 36 pre-service teachers. Additionally, in-depth insights were gained from interviews with ten participants. McClelland's motivation theories - the need for power, affiliation, and achievement - guided the analysis. The findings indicate a strong inclination toward the need for achievement, emphasizing personal growth, academic excellence, and continuous learning. Pre-service teachers are dedicated to improving their teaching skills and positively impacting students. The need for power showed moderate motivation, reflecting interest in making an impact and seeking leadership roles. The need for affiliation demonstrated moderate motivation, highlighting the importance of positive relationships and collaboration. The teaching practicum significantly influenced pre-service teachers' motivations and commitment to a teaching career. Implications for teacher education programs underscore the necessity of supporting and recognizing pre-service teachers' motivations for a successful teaching profession.